2017
DOI: 10.1097/mpg.0000000000001362
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Bleeding Secondary to Rupture of Esophageal Varices in Children and Adolescents With Cirrhosis

Abstract: The presence of gastric varices and red spots on esophageal varices were related to episodes of UGIB secondary to rupture of esophageal varices. When these findings are observed, indications for endoscopic primary prophylaxis should be evaluated. More studies are, however, necessary to better understand this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Earlier studies reported incidences ranging from 6.6 to 36%. [24][25][26][27][28][29][30] Our data showed that 24% of the children with BA developed EV bleeding at a median age of 9 months. The incidence seems comparable to earlier studies, while our cohort bled at a slightly younger age than the cohorts mentioned previously.…”
Section: Discussionmentioning
confidence: 58%
“…Earlier studies reported incidences ranging from 6.6 to 36%. [24][25][26][27][28][29][30] Our data showed that 24% of the children with BA developed EV bleeding at a median age of 9 months. The incidence seems comparable to earlier studies, while our cohort bled at a slightly younger age than the cohorts mentioned previously.…”
Section: Discussionmentioning
confidence: 58%
“…To the best of our knowledge, publications even in the recent past in regard to screening high-risk varices with PHT in children have not dealt with Baveno VI criteria. [26][27][28][29][30] However, our foremost weakness was the scarcity of the cACLD cases below 18 years, thus restricting our sample size, which meant that the plan had to be earmarked as a pilot study only. Six children (18.18%), comprising four infants with EHBA and one toddler with PFIC, continued to have high TSB, even after delivering available treatment, at 3 months of enrollment, thus acting as an effect modifier of TE values.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, due to the principal role of liver as a detoxification, damage to this organ can be very important [5,6]. There are many causes for cirrhosis of the liver, including long-term alcohol use, hepatitis B, C, and D viruses, followed by inherited diseases such as cystic fibrosis, a1-antitrypsin deficiency, galactosaemia, glycogen storage disease, Wilson syndrome, haemochromatosis, and biliary tract obstruction and biliary atresia in children [4,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) is a non-spore-forming gram-negative microaerophilic bacterium [9]. Helicobacter pylori is the most common chronic bacterial infection in humans and has infected half of the world's population.…”
Section: Introductionmentioning
confidence: 99%